Anticollocated Backstepping Observer Design for a Class of Coupled Reaction-Diffusion PDEs - Antonello Baccoli; Alessandro Pisano (Journal of Control Science and Engineering)
The state observation problem is tackled for a system of n coupled reaction-diffusion PDEs, possessing the same diffusivity parameter and equipped with boundary sensing devices. Particularly, a backstepping-based observer is designed and the exponential stability of the error system is proven with an arbitrarily fast convergence rate. The transformation kernel matrix is derived in the explicit form by using the method of successive approximations, thereby yielding the observer gains in the explicit form, too. Simulation results support the effectiveness of the suggested design.